Comparative analysis of chemical and biological properties of essential oils from fresh and dried leaves of Ocimum americanum - MUHAMMAD RUSDI; ABDUL RAHIM; HERLINA RANTE; SUBEHAN LALLO (Society for Indonesian Biodiversity, 2025)
Abstract. Rusdi M, Rahim A, Rante H, Lallo S. 2025. Comparative analysis of chemical and biological properties of essential oils from fresh and dried leaves of Ocimum americanum. Biodiversitas 26: 4976-4982. Ocimum americanum is a tropical aromatic plant native to Southeast Asia and Africa, widely used in traditional medicine. This study aimed to evaluate the impact of post-harvest drying on the chemical composition and bioactivities of the essential oils (EOs) from the leaves of O. americanum EOs were extracted via steam distillation and analyzed using Gas Chromatography-Mass Spectrometry (GC-MS). Antioxidant capacity was assessed by DPPH radical scavenging, cupric ion reducing antioxidant capacity (CUPRAC), and ferric reducing antioxidant power (FRAP) assays. Cytotoxicity against MCF-7 breast cancer cells was determined using the MTT assay, while antimicrobial activity was measured using the agar diffusion method. GC-MS analysis revealed that geranial, neral, geraniol, and nerol were the most dominant components in the essential oil from fresh leaves. The most dominant compounds in dried leaves were geranial, neral, linalool, and trans-13-octadecenoic acid methyl ester. The essential oil from fresh leaves showed higher antioxidant capacity in the DPPH radical scavenging assay, with a value of 38.08±2.17 mg TE/g EO. Conversely, the essential oil from dried leaves showed higher antioxidant capacity in the CUPRAC (278.23±1.78 mg TE/g EO) and FRAP (15.59±0.06 mg TE/g EO) assays. Fresh and dried EOs showed antimicrobial activities and cytotoxic activity against MCF-7 cells, and the dried leaf EO demonstrated better anticancer potential, with an IC?? value of 22.91 µg/mL. These findings suggest that drying significantly alters EO composition and modulates its biological activities. The findings indicate that drying extends shelf life and diversifies applications in functional foods, nutraceuticals, and phytopharmaceuticals. Optimizing post-harvest processing could improve the therapeutic value and market potential of O. americanum, supporting its sustainable use and conservation.